IDENTIFIKASI BAHAYA DAN PENENTUAN TITIK KENDALI KRITIS PROSES PENGASAPAN IKAN TUNA DI DESA MALALANDA KECAMATAN KULISUSU KABUPATEN BUTON UTARA - Febriana Muchtar; Hartati Bahar; Nurmaladewi Nurmaladewi; Lisnawaty Lisnawaty (Universitas Pahlawan Tuanku Tambusai, 2022)
The process of making smoked fish in Malalanda Village, KulisusuSub-District, North Buton Regency is carried out traditionally and from generation to generation without using modern equipment and the advance of technology. Food safety for smoked tuna needs to be a concern because it can cause public health problem called foodborne disease. This study aims to identify the hazards during the smoking process and determines the critical control point for smoked tuna processingin Malalanda Village, KulisusuSub-District, North Buton Regency. This is a descriptive research by using survey method. Based on the identification results, there are 3 types of hazards in the smoking process of tuna which are biological hazards, chemical hazards and physical hazards. The results of the identification of critical control points found 3 critical control points at the stages of tuna smoking process, namely the washing stage, the smoking stage,and selling of smoked fish stage. Keywords: Hazard Identification, Critical Control Point and Smoked Tuna